UJI KELAYAKAN LOKASI PASAR TRADISIONAL BARU DI KOTA PADANG - Yosi Suryani; Afifah Afifah; Ranti Komala Dewi (Jurnal Ilmiah Poli Bisnis, 2018)
This article aims to examine three locations for the construction of a new traditional market in Padang City, which is the result of a recommendation from a research conducted by Suryani (2015). Through this research researchers will test 1 (one) location of the development of a new traditional market in the city of Padang. That is the location between Simpang Haru Market and Bandar Buat Market. The test results provide recommendations on whether or not the location requires a new traditional market. The methodology used is testing the new location with the AHP (Analytical Hierarchy Process) method, and the assessment indicator consists of the population, location development measured by socio-economic changes, people's spending habits around the location of the people's market development plan, the purchasing power of residents around the location of market development plans people, differences in social status, number, area, type and location of old markets, accessibility, and physical condition of the natural environment around the planned location of the construction of a new people's market. The results of the study concluded that the testing of the location between the Simpang Haru Market and the Bandar Buat Market resulted in a range of judgments that were in a position quite high. Figures with a fairly high predicate provide recommendations that in these locations require a traditional maid market that can serve the needs of society optimally in areas that are not included in the broad slice of the nearest traditional market